Characterizing Traumatic Brain Injury and Its Association with Losing Stable Housing in a Community-based Sample. (March 2022) - Stubbs, Jacob L.; Thornton, Allen E.; Gicas, Kristina M.; O'Connor, Tiffany A.; Livingston, Emily M.; Lu, Henri Y.; Mehta, Amiti K.; Lang, Donna J.; Vertinsky, Alexandra T.; Field, Thalia S.; Heran, Manraj K.; Leonova, Olga; et al.
Objective: Traumatic brain injury (TBI) is increasingly recognized as a common and impactful health determinant in homeless and precariously housed populations. We sought to describe the history of TBI in a precariously housed sample and evaluate how TBI was associated with the initial loss and lifetime duration of homelessness and precarious housing. Method: We characterized the prevalence, mechanisms, and sex difference of lifetime TBI in a precariously housed sample. We also examined the impact of TBI severity and timing on becoming and staying homeless or precariously housed; 285 precariously housed participants completed the Brain Injury Screening Questionnaire in addition to other health assessments. Results: A history of TBI was reported in 82.1% of the sample, with 64.6% reporting > 1 TBI, and 21.4% reporting a moderate or severe TBI. Assault was the most common mechanism of injury overall, and females reported significantly more traumatic brain injuries due to physical abuse than males (adjusted OR = 1.26, 95% CI = 1.14 to 1.39, P < 0.0001). The first moderate or severe TBI was significantly closer to the first experience of homelessness ( b = 2.79, P = 0.003) and precarious housing ( b = 2.69, P < 0.0001) than was the first mild TBI. In participants who received their first TBI prior to becoming homeless or precariously housed, traumatic brain injuries more proximal to the initial loss of stable housing were associated with a longer lifetime duration of homelessness (RR = 1.04, 95% CI = 1.02 to 1.06, P < 0.0001) and precarious housing (RR = 1.03, 95% CI = 1.01 to 1.04, P < 0.0001). Conclusions: These findings demonstrate the high prevalence of TBI in this vulnerable population, and that aspects of TBI severity and timing are associated with the loss and lifetime duration of stable housing.